Climate change adaptation under a social capital approach – An analytical framework for small islands. (August 2015) - Petzold, Jan; Ratter, Beate M.W.
Abstract: Small islands are more vulnerable to the impacts of climate change than most continental regions. However, islands also feature a high degree of resilience through resources from dense social networks, such as collective action, norms of reciprocity, and relations of trust. Therefore, we argue that these resources – generally defined as social capital – are particularly relevant for climate change adaptation on small islands. Current research on the role of social capital for communities covers many different aspects, such as local knowledge, economic development, and political capacity. But effective adaptation relies on understanding the role of social capital for these aspects in connection to the specific impacts of climate change – a holistic approach is needed. Based on empirical case studies we developed an analytical framework that provides a step-by-step approach to help analyse the potential of social capital for the adaptation to climate change in island-specific case studies. These steps, among others, include an assessment of social capital, hazard mapping, and the analysis of political and economic capacity. Moreover, the framework suggests methods on how to analyse these steps. Highlights: Small islands are more vulnerable to the impacts of climate change than continental regions. Islands feature a high degree of resilience through dense social networks, collective action, norms of reciprocity, relations of trust. Social capital is particularly relevant for climate change adaptation on small islands. A step-by-step approach to analyse potentials of social capital for the adaptation to climate change. An assessment of social capital, hazard mapping, and the analysis of political and economic capacity.